OCT angiography analysis of choriocapillaris vascular density in different stages of age-related macular degeneration - Savastano, Maria Cristina; Fossataro, Claudia; Carlà, Matteo Mario; Fantozzi, Chiara; Falsini, Benedetto; Savastano, Alfonso; Rizzo, Clara; Kilian, Raphael; Rizzo, Stanislao (Frontiers in Ophthalmology, 2022)
Objectives: To analyze the choriocapillaris’ vessel density (CVD) of eyes at different stages of Age-related Macular Degeneration (AMD) with Optical Coherence Tomography Angiography (OCTA). Methods: This is a prospective observational cross-sectional study on 21 age-matched healthy eyes and 84 eyes with AMD (i.e., early AMD, late AMD, Geographic Atrophy [GA], and disciform scar AMD). OCTA was used to automatically measure the CVD (%), on both the whole macula and the foveal area, in a layer going from 9 µm above to 30 µm below the Bruch’s membrane. Furthermore, in the GA subgroup, the extension of the Ellipsoid Zone (EZ) interruption and the area of macular chorio-retinal atrophy was analyzed. Results: Macular CVD was significantly lower in the GA, late AMD and disciform scar AMD-subgroups compared to controls (respectively, p=0.0052; p<0.0001; p=0.0003), whereas it did not significantly vary in the early AMD-group (p=0.86). A significant difference between the early AMD and both the late AMD and the disciform scar AMD subgroups was also found (p=0.0009 and 0.0095, respectively). When comparing the foveal CVD of healthy and AMD eyes, a significant difference was found with every AMD-subgroup (early AMD, p=0.011; GA, p<0.0001; late AMD, p<0.0001; disciform scar AMD, p<0.0001). Furthermore, in the GA subgroup, the CVD had an inverse correlation with both the extension of the EZ-interruption (p=0.012) and with the calculated chorio-retinal atrophic area (p=0.009). Conclusions: OCTA could play a crucial role in the categorization of AMD, allowing for the evaluation of gradual flow impairment at different stages of the disease. Moreover, the detection of a decreased macular and foveal CVD may shed light on the pathogenesis of AMD.